Code-Mixing in Student Interaction of Japan UKM Members in State Polytechnic of Bali - Harisal Harisal; Ni Putu Somawati; Wahyuning Dyah; Kanah Kanah (Universitas Diponegoro, 2021)
Code-Mixing often occurs in a place where there are various ethnicities, tribes, languages, and various cultures. One of them is at the State Polytechnic of Bali. This study aims to describe the form of code-mixing that appears in the interactions of Students Extracurricular Unit of Japan called UKM Jepang members of the State Polytechnic of Bali and explain the motives for using code-mixing in the interactions. The data used in this study is the result of the interaction of students who are members of the UKM Jepang, State Polytechnic of Bali, indicated to cause Code-Mixing both offline and online. Furthermore, the research approach used in this study is a qualitative approach with the type of research being descriptive research. The results showed that the form of Code-Mixing that occurred in students of Japanese UKM members of the State Polytechnic of Bali occurred in mixing nouns, verbs, adjectives, and adverbs. The motives that cause the emergence of code-mixing include the consideration of the interlocutor, namely members of UKM Jepang who both understand Japanese vocabulary. Besides, some special terms in Japanese are considered more appropriate to be conveyed by students on certain topics related to Japan, and they deliberately mix the code to make the conversation more interesting. On the other hand, Some Japanese vocabulary has no meaning that can be spoken in conversation in Indonesian, which causes students to use the term and become a new 'vocabulary' in Indonesian. They accidentally did lexical borrowing to meet the language barrier and cause code-mixing.